Numerical investigation of gas‐liquid displacement between borehole and gassy fracture using response surface methodology. Issue 3 (15th November 2019) - Ma, Tianshou; Tang, Tao; Chen, Ping; Li, Zhilin; Liu, Shaohu
Abstract: Gas‐liquid displacement occurs often in fractured gas reservoirs, and can cause gas kick and mud leakage, resulting in a very high risk of losing well control. To analyze gas‐liquid displacement between borehole and gassy fracture, we used computational fluid dynamics to simulate its behaviors. We also used response surface methodology (RSM) to design numerical experiments. The effects of fracture width, bottom‐hole differential pressure, mud density, mud viscosity, and mud displacement were taken into account. We used RSM to determine the influence of the multifactor interaction of gas‐liquid displacement and established an empirical formula for the gas displacement rate. The results show that gas‐liquid displacement is proportional to fracture width, bottom‐hole differential pressure, mud density, and mud displacement; however, the displacement is inversely proportional to mud viscosity. The sensitivity sequence of the gas‐liquid displacement rate is fracture width > bottom‐hole differential pressure > mud viscosity > mud density > mud velocity. The impact of fracture width is clearly higher than that of the other factors, while the mud velocity has almost no impact. Our established empirical formula can be used to predict bottom‐hole gas kick and drilling mud leakage and to inversely predict the fracture width and formation gas pressure. Abstract : Gas‐liquid displacement behaviors between borehole and gassy fracture were simulated using CFD, and RSM was used to design numerical experiments of gas‐liquid displacement. The effects of fracture width, bottom‐hole differential pressure, mud density, mud viscosity, and mud displacement were taken into account. Response surface methodology was used to determine the empirical formula for the gas displacement rate. The influence of the multifactor interaction on gas‐liquid displacement was investigated using RSM.